Pengaruh Good Corporate Governance Dan Manajemen Risiko Terhadap Kinerja Keuangan - Gollu, Matilda Roswita; Utami, Endang Sri (Value : Jurnal Manajemen dan Akuntansi, 2024)
The phenomenon of the emergence of GCG began to be known because it was discussed repeatedly along with the increasing public awareness. Both the government and management need a mechanism that can increase openness. Good Corporate Governance is growing in many companies, both public and private. This research aims to determine the Effect of Good Corporate Governance and Risk Management on Banking Financial Performance (Empirical Study of Commercial Banks Listed on the Indonesia Stock Exchange in 2021-2023). A quantitative approach was used in this study. This study uses the banking sub-sector object listed on the Indonesia Stock Exchange (IDX) with a time span of 2021-2023. The sample method used is purposive sampling with a population consisting of 47 banking companies, resulting in 16 companies with a total sample of 48 analyzed. The study output shows that GCG and Risk Management have a positive impact on Banking Performance. Thus, the research results show that GCG and Risk Management tend to have a high probability ratio, namely more stable and high finances with Banking Financial Performance. This finding can be a guide for shareholders in making decisions in the company.